The Accounting information system design of Avia Jaya Savings and Loans Cooperative Palu City - Kevin, Kevin; Yamin, Nina Yusnita; Meldawati , Lucyani; Afdhal, Muhammad (Politeknik Ganesha Medan, 2022)
Accounting information systems are very important for a financial organization, one of which is a financial information system in cooperatives. Cooperatives that aim for the welfare of their members must pay attention to their accounting information system, so that it does not become an obstacle in the future. The design of an accounting information system in cooperatives is intended to help cooperatives carry out the process of cooperative activities easily. This study aims to design an accounting information system at the Avia Jaya Member Cooperative. This research is a qualitative research with a case study approach which includes system analysis and continued with the design of information systems. The system design method used in this research is the System Development Life Cycle (SDLC) method or the system development life cycle with the waterfall model. The design of information systems is made using flowcharts, Data Flow Diagrams and system implementation. The results of this study based on the system design using Microsoft Excel based on Visual Basic for Applications at the Avia Jaya employee cooperative, it was found that there was a process in the recording of deposit and loan transactions, as well as the resulting reports. The process of making an accounting information system is carried out based on the results of a case study by analyzing the Avia Jaya Employee Cooperative which does not yet have a system so that it hinders the process of running the accounting information system in the cooperative. The existence of this application design can make it easier for cooperative members to carry out the process of preparing financial reports which previously recorded manually into digital records and make it easier for users to make decisions.